2014
DOI: 10.1093/cercor/bhu186
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsomedial Prefrontal Cortex Plays a Causal Role in Integrating Social Impressions from Faces and Verbal Descriptions

Abstract: Several neuroimaging studies point to a key role of the dorsomedial prefrontal cortex (dmPFC) in the formation of socially relevant impressions. In 3 different experiments, participants were required to form socially relevant impressions about other individuals on the basis of text descriptions of their social behaviors, and to decide whether a face alone, a trait adjective (e.g., "selfish"), or a face presented with a trait adjective was consistent or inconsistent with the impression they had formed. Before d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 71 publications
10
57
0
Order By: Relevance
“…This is in line with prior TMS evidence showing that interfering with dmPFC activity did not impact perceived face trustworthiness when the judgment was exclusively based upon facial appearance (Ferrari et al , 2016, supplementary data), and with prior neuroimaging evidence indicating that evaluations uniquely based on face appearance are likely to elicit responses in subcortical (e.g., amygdala) more than in cortical regions (Said et al , 2009; Baron et al , 2011; de Gelder et al , 2012, Fouragnan et al , 2013; Mende-Siedlecki et al , 2013; but see Bzdock et al . , 2012a).…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with prior TMS evidence showing that interfering with dmPFC activity did not impact perceived face trustworthiness when the judgment was exclusively based upon facial appearance (Ferrari et al , 2016, supplementary data), and with prior neuroimaging evidence indicating that evaluations uniquely based on face appearance are likely to elicit responses in subcortical (e.g., amygdala) more than in cortical regions (Said et al , 2009; Baron et al , 2011; de Gelder et al , 2012, Fouragnan et al , 2013; Mende-Siedlecki et al , 2013; but see Bzdock et al . , 2012a).…”
Section: Discussionsupporting
confidence: 90%
“…In a previous work (Ferrari et al, 2016), we found that online TMS over the dmPFC delayed fast dichotomous (yes/ no) responses when participants had to decide whether a faceadjective pair (for instance, a face accompanied by the adjective "selfish") matched the impression they had formed about that agent by reading a description of his behavior. In that work, it was the target stimulus to be "congruent" or "incongruent" with the impression formed, and response accuracy could be measured because the trait-adjective was clearly either in line or in contrast with the behavior described (hence, not surprisingly, accuracy was very high, above 90%).…”
Section: Discussionmentioning
confidence: 84%
“…Neuroimaging and brain stimulation evidence suggests that forming social impressions about others and/or judging their trustworthiness involves the medial prefrontal cortex (mPFC) (Cattaneo, Mattavelli, Platania, & Papagno, 2011;Cloutier, Gabrieli, O'Young, & Ambady, 2011;Ferrari et al, 2016;Ma et al, 2012;; Mende-Siedlecki, Baron, & Todorov, 2013;Mende-Siedlecki, Cai, & Todorov 2012;Schiller, Freeman, Mitchell, Uleman, & Phelps, 2009). Interestingly, this region is also involved in processing socially relevant emotions (such as arrogance or guilt) beyond basic emotions (Jankowski & Takahashi, 2014;see also D'Agata et al, 2011).…”
mentioning
confidence: 99%
“…Although the dlPFC subserves multiple functions and seems to regulate various emotional states969798, recent studies implicate the dlPFC in sadness and depression99, especially during cognitive reappraisal and regulation of this emotion100. In such tasks, reappraisal minimizes the experience of negative affect after viewing sad stimuli and amygdala responses are dampened, possibly via the inhibitory function of the dlPFC101.…”
Section: Discussionmentioning
confidence: 99%